Furosemide in pediatric intensive care: a retrospective cohort analysis - Gaetani, Melany; Parshuram, Christopher S.; Redelmeier, Donald A. (Frontiers in Pediatrics, 2024)
Furosemide is the most commonly used medications in pediatric intensive care. Growing data indicates improved hemodynamic stability and efficacy of furosemide infusions compared to intermittent injections, thereby suggesting furosemide infusions might be considered as first line therapy in critically ill, paediatric patients. The objective of this study is to examine furosemide treatment as either continuous infusions or intermittent injections and subsequent patient outcomes. This is a retrospective cohort analysis of patients treated in a pediatric intensive care unit (ICU) over a nine year period (July 31 st 2006 and July 31, 2015). Eligible patients were admitted to either the general pediatric or cardiac specific ICU for a duration of at least 6 hours and who received intravenous furosemide treatment. A total of 7478 patients were identified who received a total of 118,438 furosemide administrations for a total of 113 951(96%) intermittent doses and 4,487 (4%) infusions running for a total of 1,588,750 hours. A total of 5996 (80%) patients received exclusively furosemide injections and 1482 (20%) patients received at least one furosemide infusion. A total of 193 patients died during ICU admission, amounting to 87 (6%) of the 1482 patients who received an infusion and 106 (2%) of the 5996 who received intermittent injections. Multivariable regression analysis showed no statistically significant decrease in adjusted mortality for patients who received furosemide injections compared to furosemide infusions (aOR 1.20, CI 0.76 -1.89). This retrospective study observed similar mortality for patients who received furosemide infusions compared to furosemide injections. More research on furosemide in the ICU could provide insights on fluid management, drug effectiveness, and pharmacologic stewardship for critically ill children.